Sin, Illness, and Relational Healing: A Contextual Theology Study of the GPM Kaibobo Congregation - Melinda Matuankotta; Agustinus M L. Batlajery; Ricardo F. Nanuru (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2026)
This study examines how the GPM Kaibobo congregation understands sin and illness not only as moral or medical problems, but as disruptions in relationships among human beings, nature, and God. It analyzes these interpretations through contextual theology and explores the interaction of customary traditions, medical knowledge, and ecclesial responses. Using a qualitative design, data were collected through interviews with thirteen participants and supported by relevant theological literature. The findings indicate that sin is understood as a violation against God, customary law, and nature, while illness is frequently interpreted as a sign of disturbed communal, ecological, and spiritual balance. The church therefore plays a crucial role in helping the congregation interpret suffering through Christian faith while encouraging dialogue with indigenous wisdom and modern healthcare. The study concludes that Kaibobo’s holistic cosmology enriches Indonesian contextual theology, particularly Bevans’ anthropological and praxis models, and supports transformative, culturally grounded, and medically responsible pastoral ministry.